2001
DOI: 10.1002/polb.1064
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in poly(N‐isopropyl acrylamide)/water solutions. II. Salt effects on cloud‐point curves and gelation

Abstract: The cloud-point temperatures (T clo 's) of poly(N-isopropyl acrylamide) (PNI-PAM)/water solutions with NaCl, NaBr, or NaI were measured. All these salts reduced the T clo 's of PNIPAM/water solutions to different extents, in the following order: NaCl Ͼ NaBr Ͼ NaI. The higher the concentration of the added salt was, the more greatly T clo dropped. A dynamic viscoelasticity investigation of the PNIPAM/water solutions with the salts indicated that during phase separation, the system changed from a homogeneous flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
2
25
1
Order By: Relevance
“…22 An alternative explanation is that the ions disrupt the hydration structure at the water-solute interface. 23 New theories, such as specific ion binding, have also been proposed to explain the Hofmeister series. 14,15 Although the effects of salt on some gelation systems, including MC, have been investigated in our earlier studies, 12,24,25 few reports have been made on the effects of salt on the gelation of HPMC, even though HPMC has more applications in pharmaceutics.…”
Section: Introductionmentioning
confidence: 99%
“…22 An alternative explanation is that the ions disrupt the hydration structure at the water-solute interface. 23 New theories, such as specific ion binding, have also been proposed to explain the Hofmeister series. 14,15 Although the effects of salt on some gelation systems, including MC, have been investigated in our earlier studies, 12,24,25 few reports have been made on the effects of salt on the gelation of HPMC, even though HPMC has more applications in pharmaceutics.…”
Section: Introductionmentioning
confidence: 99%
“…According to the schematic description given in Figure 14, PNIPA sequences inserted between PDMA side-chains collapse above their transition temperature and form sticky globules that self-associate into a percolating 3D structure. This mechanism can be compared to the one reported with aqueous solutions of pure linear PNIPA as they also form physical networks during phase separation above some overlap concentration [52,53].…”
mentioning
confidence: 99%
“…Moreover, if the salt concentration is decreased the collapse temperature increases proving that the solubility of PNIPAM in water is highly dependent on the temperature and the salt concentration. [26,30] The LCST of bulk and encapsulated PNIPAM with different ions is investigated with DSC and confocal microscopy, respectively. Capsules filled with PNIPAM were also measured with DSC, but due to the low sensitivity of the instrument the LCST of the encapsulated PNIPAM could not be observed.…”
Section: Taking CLmentioning
confidence: 99%
“…Yang et al have shown that objects which induce water structure, decrease the LCST by promoting hydrophobic interactions. [26] The difference between the LCST of pure PNIPAM in the bulk and inside the capsules arises from the increased order of the structure of the water inside the polyelectrolyte capsule wall. [27] The result is that either the capsule wall components or their complement are structuring the water, which brings about a 2 8C difference in the collapse temperature of the encapsulated and bulk PNIPAM.…”
mentioning
confidence: 99%